2014
DOI: 10.1186/1471-2334-14-308
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the epidemiology of hepatitis E virus in Africa

Abstract: BackgroundHepatitis E Virus (HEV) infection is a newly recognized serious threat to global public health and Africa is suspected to be among the most severely affected regions in the world. Understanding HEV epidemiology in Africa will expedite the implementation of evidence-based control policies aimed at preventing the spread of HEV including policies for the use of available resources such as HEV vaccines.MethodsHere we present a comprehensive review of HEV epidemiology in Africa based on published data. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 112 publications
(155 reference statements)
7
127
1
2
Order By: Relevance
“…HAV and HEV are waterborne viruses that usually cause acute hepatitis without progressing to chronic liver diseases (5, 6). According to the Global Burden of Disease study, 101.7 million cases of HAV and 28.4 million cases of HEV infection occurred worldwide in 2013 (7).…”
Section: Introductionmentioning
confidence: 99%
“…HAV and HEV are waterborne viruses that usually cause acute hepatitis without progressing to chronic liver diseases (5, 6). According to the Global Burden of Disease study, 101.7 million cases of HAV and 28.4 million cases of HEV infection occurred worldwide in 2013 (7).…”
Section: Introductionmentioning
confidence: 99%
“…Data from earlier studies in Tanzania suggested either lack of exposure or low levels of HEV among women ( 7 , 8 ). A review of the epidemiology of HEV in Africa by Kim et al ( 9 ) provides a listing of seroprevalence of HEV antibodies in various African countries.…”
mentioning
confidence: 99%
“…HEV seroprevalence estimates from Africa vary widely though seroprevalence estimates of over 60% within the general population have not been found frequently, even during or after large outbreaks 5,23. Even in “hyperendemic” areas, including Nepal and Bangladesh, documented seroprevalence has typically been estimated at levels well below those in this study 24.…”
Section: Discussionmentioning
confidence: 58%